Can intra-articular injection of freeze-dried platelet-derived factor concentrate regenerate articular cartilage in the knee joint? - Shirata, Tomohiko (Regen Ther, 2019)
Freeze-drying methods not only enable the delivery of growth factors using platelets, but also extend the shelf-life of platelet concentrates. The present study shows the clinical results of treating knee osteoarthritis with freeze-dried platelet-derived factor concentrate (PFC). While it improved pain, activities of daily living, sports and recreational activities, and knee-related quality of life, it did not significantly improve symptoms other than pain, such as restricted range of motion and mechanical symptoms. As such, the treatment effect may be attributed to anti-inflammatory action rather than actual cartilage regeneration.